Millionfold Resistance Change in Ferroelectric Tunnel Junctions Based on Nickelate Electrodes. (8th January 2016) - Bruno, Flavio Y.; Boyn, Sören; Fusil, Stéphane; Girod, Stéphanie; Carrétéro, Cécile; Marinova, Maya; Gloter, Alexandre; Xavier, Stéphane; Deranlot, Cyrile; Bibes, Manuel; Barthélémy, Agnès; Garcia, Vincent
Abstract : When electrons tunnel through an ultrathin ferroelectric, large variations of the tunnel transmission can result from the switching of the ferroelectric polarization. High‐quality ultrathin films of BiFeO3 with atomically flat terraces and single unit‐cell steps on epitaxial electrodes of LaNiO3 have been fabricated. The films crystallize in the pure polymorph of BiFeO3 with giant tetragonality; they show tunnel transport characteristics up to ten unit cells and a clear ferroelectric signal from scanning probe techniques. Sub‐micrometer solid‐state tunnel junctions defined from these heterostructures are switched by nanosecond voltage pulses. A complete reversal of the ferroelectric polarization results in large variations of the junction resistance, but partial switching of the polarization favors the reversibility of the resistance switching. Finally, the electrical transport characteristics of fully patterned tunnel junctions are investigated in the 300 K–80 K temperature range. Owing to the low resistivity of LaNiO3 electrodes, the junctions display record tunnel electroresistance values of more than 10 6 at 80 K combined with weak temperature dependences as expected for electron tunneling transport. These results will motivate further work to trigger metal–insulator transitions by electric‐field effects in ferroelectric tunnel junctions combined with strongly correlated nickelates. Abstract : A giant tunnel electroresistance is achieved by combining super‐tetragonal BiFeO3 ultrathin films with low‐resistivity LaNiO3 electrodes. Arrays of sub‐micrometer solid‐state junctions are switched by nanosecond voltage pulses. The ferroelectric switching process is investigated by piezoresponse force microscopy imaging and tunnel transport measurements. These experiments will stimulate the search for sharp polarization‐induced metal–insulator transitions in strongly correlated oxide nickelates.